ELABORATION OF THE BATCH OF THE PROGRAMS FOR CELESTIAL MECHANICS FOR THE COMPUTATION OF THE ASTRONOMICAL EPHEMERIS - Mikhalchuk, V. V. (Одеські астрономічні публікації, 2017)
The batch of the programs for celestial mechanics are elaborated in order to obtain the ephemeris of the Sun, the Moon, the planets and their satellites, the asteroids, the comets, the binary stars, the variables stars, determination of the conditions of the visibility these the celestial bodies at any point of the surface of the Earth, as well as predict the astronomical phenomena’s at the celestial sphere and their circumstances.